Neurocognitive and neurodevelopmental impact of prenatal methamphetamine exposure: A comparison study of prenatally exposed children with nonexposed ADHD peers. Issue 2 (3rd April 2019) - Brinker, Michael J.; Cohen, Jodie G.; Sharrette, Johnathan A.; Hall, Trevor A.
ABSTRACT: Prenatal methamphetamine exposure has become an increasingly pervasive concern, especially in rural-based populations and populations of lower socioeconomic status. While research has begun to highlight the effects of prenatal methamphetamine exposure, the long-term impact of this exposure remains an under-investigated topic. This study attempts to investigate the neurocognitive and neurodevelopmental effects of prenatal methamphetamine exposure by comparing the index and full-scale IQ scores on the WISC-IV between a sample of clinically referred children prenatally exposed to methamphetamine ( N  = 80) and a sample of clinically referred nonexposed children diagnosed with ADHD ( N  = 44). Children prenatally exposed to methamphetamine showed significantly lower scores on all WISC-IV domains when compared to peers with ADHD. When taking into account polysubstance exposure to alcohol, these differences remained statistically significant, with the exception of the Processing Speed Index (PSI); children reported to have been prenatally exposed to methamphetamine and to alcohol (PME) remained below ADHD peers on all other WISC-IV index scores. Within the prenatally exposed sample, regression analyses indicated that age was a significant negative predictor of PSI scores. Overall findings suggest that prenatal methamphetamine exposure is associated with a notable cognitive impact independent of polysubstance exposure to alcohol, and that the impact of this exposure on processing speed skills may become more pronounced with age.